2008
DOI: 10.1143/jjap.47.6910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residual Carbon and Hydrogen Atoms on Electrical Property of GaAsN Films Grown by Chemical Beam Epitaxy

Abstract: The electrical behavior of nitrogen-hydrogen (N-H) complexes and carbon (C) atoms in GaAsN films grown by the chemical beam epitaxy (CBE) method have been studied by comparing H concentrations and hole concentrations. The contributions of H and C concentrations ([H] and [C]) to ionized impurity scattering have been also investigated. In the GaAsN films, there were three acceptor levels (A0, A1, and A2). The energy levels of A1 and A2 were 130 and 55 meV, respectively. The concentration of the deepest acceptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
5
10
1
Order By: Relevance
“…The thermal ionization energy of this energy level was estimated in the temperature range 70 to 100 K to be between 0.1 and 0.2 eV. It is in conformity with the theoretical calculations, which suggested the existence of a N-related hole trap acceptor-like defect with an activation energy within 0.03 and 0.18eV above the VBM of GaAsN (Janotti et al, 2003;Suzuki et al, 2008). Experimentally, a deep acceptor level, A2, was confirmed in CBE grown undoped GaAsN with ionization energies of E A1 = 130 ± 20 meV .…”
Section: Deep N-h Related Acceptor State H2supporting
confidence: 82%
“…The thermal ionization energy of this energy level was estimated in the temperature range 70 to 100 K to be between 0.1 and 0.2 eV. It is in conformity with the theoretical calculations, which suggested the existence of a N-related hole trap acceptor-like defect with an activation energy within 0.03 and 0.18eV above the VBM of GaAsN (Janotti et al, 2003;Suzuki et al, 2008). Experimentally, a deep acceptor level, A2, was confirmed in CBE grown undoped GaAsN with ionization energies of E A1 = 130 ± 20 meV .…”
Section: Deep N-h Related Acceptor State H2supporting
confidence: 82%
“…2(b). Similar bellshaped curves are observed for C-doped p-type GaAsN alloys grown by CBE [38], where C originates from metalorganic sources. Thus, the bell-shaped curves are probably common for p-type GaAsN alloys.…”
Section: Electrical Characterizationsupporting
confidence: 76%
“…In addition, alloy scattering should be considered for alloy semiconductors. As for GaAsN alloys, several authors have reported that N atoms act as a scattering center probably due to a local fluctuation of N composition in GaAsN alloys from Hall-effect measurements [38,39]. It should be noted that the N composition of 1% corresponds to the N concentration of $2 Â 10 20 cm À 3 ; this N Activation energy E a is estimated to be 22(7 5) meV ( Fig.…”
Section: Electrical Characterizationmentioning
confidence: 89%
See 1 more Smart Citation
“…Concerning E HC2 , it comes closer to the VBM of GaAsN with increasing [N] in the films. This can be explained through the Poole−Frenkel emission phenomenon, since the maximum magnitude of the electric field near the junction increases simultaneously with the junction capacitance and affects considerably the thermal emission of majority carriers from HC2 [7]. Further, the mean value of E HC2 is in conformity with the theoretical calculation and approximately identical to that calculated from the temperature dependence of free hole concentration in CBE grown p-type GaAsN [2,6].…”
Section: Relationship Between a N-related Hole Trap And Ionized Accepsupporting
confidence: 75%